New Urbanism : A Comparative Analysis Between Traditional Village and Housing Estate - Bhakti Alamsyah (Bandar Lampung University (UBL), 2014)
Rapid urbanization has been a critical issue to urban environments. The immediate and most critical urban environment problems faced by several cities, such as Jakarta and Surabaya, are drinking water, sanitation, traffic and industrial pollution, land degradation, and traffic congestion. It is believed that New Urbanism is thought to be an alternative approach to address the above issues. This paper also discusses the physical and social character of two settlement i.e. housing estate and traditional village. The comparative analysis will be discussed further by using case studies. Consequently the issues on New Urbanism will be related to the other aspect of new development in the future.